Why leading is (almost) as important as winning - Alves, Hans; Vogel, Tobias; Grüning, David; Mata, André (Cognition, 2023)
Competitions in sports, business, or politics often provide perceivers with cumulative standings over time. Recent research suggests that people fail to accurately update their impressions from cumulative observations as they are influenced by previous standings. This cumulative redundancy bias (CRB) implies that competitors that are leading during a competition will receive more favorable evaluations, over and beyond their eventual success or failure. While the CRB has far-reaching implications, its underlying mechanisms are not fully understood. We present data from four experiments in which we modified the standard CRB task by adding a step-by-step procedure to track the dynamics of perceivers' impressions during the competition. We also manipulated the length of the competition and tested different possible explanations for the CRB. Results suggest that the CRB is a robust phenomenon that constitutes an actual bias and that is best explained by an additive effect of cumulative redundancy.
Erstmals am 29. Oktober 2022 online veröffentlicht
Gesehen am 22.12.2022